THE IMPORTANT FEATURES OF POSTMODERN IDEAS IN ENGLISH AND AMERICAN LITERATURE - Sulaymonova , Dildora (Innovative Development in Educational Activities, 2023)
The postmodern is a philosophical way of thinking about life that is not confined by conventional cultural conventions. This literary period started in the 70 - 90ss in Britain and America. It is a new phenomenon and has features which make it different from modernism and realism. If modernism is seen as the movement that cleared the way for a new era in English literature, postmodernism is the descendant that was created from the principles of modernism and developed into a super force that has dominated for decades. It is difficult to understand the author’s intentions in postmodern era as the literary devices employed in a work make it quite complex. The reader has to focus hard to understand where the fragments are leading and where they are joining together to reveal the plot. It sounds difficult, but the use of simple language by postmodern writers helps a lot in understanding the complex structure. However, it is not enough for fully realizing of this period’s ideas in literary works. The main purpose of this article to demonstrate the main characteristics of postmodernism and analyze the writers’ ideas about this term in English and American literature.